Temperature and children’s dietary diversity: Evidence from India - Rajkhowa, Pallavi; Chakrabarti, Suman (Elsevier, 2024)
Children’s exposure to heat is related to both chronic and acute nutritional status. However, there is limited empirical evidence on how a rise in temperature affects dietary quality. Using the most recent rounds of the Demographic Health Survey for India, conducted in 2015–16 and 2019–20, combined with geospatial data from various sources, this study empirically explores the relationship between temperature and dietary diversity of children in the age group of 6 to 23 months. The study highlights that higher temperatures are associated with a modest yet statistically significant decrease in the dietary diversity of children aged 6 to 23 months. We also find that, while minor temperature variations may have minimal effects, larger shifts within specific temperature ranges can lead to more pronounced alterations in children’s dietary diversity. Moreover, factors such as children’s age, historical climate context, and seasonality influence the magnitude of this relationship. Additionally, access to infrastructure and maternal education significantly mediate the adverse effects of temperature on children’s dietary patterns, highlighting the importance of targeted interventions in vulnerable communities..